PENGARUH LOAD CAPACITY LISTRIK TERHADAP EFFISIENSI TURBIN UAP MODEL C6-R8-ER : STUDY KASUS PADA PT. SURYA BORNEO INDUSTRI - Tratama, Teddy; Aspiyansyah, Aspiyansyah; Harianto, Agus; Rahmandika, Kukuh (Jurnal Rekayasa Mesin, 2024)
Steam turbines are widely used at many industrial. The purpose of this research was to study the effect of load capacity on steam flow mass rate.  Load Capacity is directly proportional to the steam flow mass rate to increase Steam turbine power. While the effect of load capacity on steam turbine efficiency, where it shows the actual performance of the steam turbine which is very important to minimize operating costs. The highest thermal efficiency of 21.49% and the lowest thermal efficiency of 20.17% in the load capacity variation showed that the steam turbine can still be categorized in good condition where the operating period has reached 5 years. It is necessary to carry out preventive maintenance on steam turbine components so that they remain reliable in supporting the company's operational and production activities.